2014
DOI: 10.1002/14651858.cd010796.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for treating hip impingement (femoroacetabular impingement)

Abstract: There is no high quality evidence examining the effectiveness of surgery for femoroacetabular impingement. There are four ongoing studies, which may provide evidence for the benefit and safety of this type of surgery in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…There is currently no high-level evidence to support the choice of a definitive treatment for FAI syndrome 22 23. For any one patient, the panel agreed that it is appropriate to consider the different treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no high-level evidence to support the choice of a definitive treatment for FAI syndrome 22 23. For any one patient, the panel agreed that it is appropriate to consider the different treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…There is no high quality evidence examining the effectiveness of surgery for FAI, as there are as yet no randomised clinical trials available. 4 A limited number of studies have produced robust prospective data demonstrating a significant improvement in surgical outcome at two or more years. A recent review showed improved outcome between 82% and 94% after two years.…”
Section: Results Of Fai Surgerymentioning
confidence: 99%
“…19 There are a number of randomised controlled trials in progress which should provide appropriate highquality evidence in the future.…”
Section: Conservative Treatmentmentioning
confidence: 99%